IMAGE OF A FAMILY IN TEENAGERS WHO HAVE EXPERIENCE OF LIVING IN CLOSED INSTITUTIONS - S. S. Solonchenko (Вестник университета)
The purpose of this article is to analyse the results of research aimed at identifying features of the family image in adolescents who have experience of living in closed institutions. Based on the results of the study significant differences in the family image of graduates of closed institutions and their peers who are raised in families have been revealed. The image of a family of domestic teenagers is clearly defined, structured, with distributed intra-family roles. Independence and socialization of teenagers brings to the image of the family a serious and responsible attitude to family relations. The key role in the image of a family of home teenagers is played by such qualities as determination, selfsufficiency, independence. Openness is a quality that distinguishes domestic teenagers from their peers from foster families and closed institutions. Home teenagers give meaning to relationships, household sphere and symbols in the image of the family. The image of the family in teenagers who are raised in blood families is described in more detail than in their peers from closed institutions and foster families.